(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In today's digital age, the rapid advancement of technology has brought about significant changes in how information is collected, stored, and shared. This paper explores the profound impact of technology on privacy laws, examining the evolution of privacy regulations in response to technological innovations. It delves into key areas such as data collection practices, surveillance technologies, cybersecurity threats, and the challenges posed by emerging technologies like artificial intelligence and biometrics. By analyzing case studies and legislative developments, this research paper aims to provide insights into the complex interplay between technology and privacy laws, as well as the implications for individuals, businesses, and society as a whole.